Study of insulin resistance and antioxidant vitamin status in prostate cancer patients - Vardhan, S. Prasanth; Krishnamma, M.; Naidu, J. N.; Naidu, M. Prasad (International Journal of Research in Medical Sciences, 2017)
The incidence of prostate cancer is 5 per 100000 in southern and eastern Asia. Both genetic and environmental factors have been implicated in its etiology. The mitogenic and growth stimulatory effects of Insulin growth factor may be involved in prostate carcinogenesis. To evaluate serum insulin and insulin resistance was passed by HOMA- IR. Prostatic specific antigen passed by immune-enzymatic assay. Vitamins were estimated by high performance liquid chromatography. In our study 30 prostate cancer patients aged 60-80years were taken as cases. 30 normal age matched disease free person were taken as controls in both groups, Insulin resistance and antioxidant vitamin status was studied. In the present study, the value of HOMA-IR was (P <0.05) is significantly higher compare to controls. Serum vitamin E and vitamin C values for cases was reduced (P <0.05) significantly lower than controls. The development of prostate cancer is a multistep process. Hyperinsulinemia associated with insulin resistance may play a role in pathogenesis of prostate cancer. Prostate cancer cells generate high levels a ROS.